Is primary stability the gold standard factor in implant success - Md Nazish Alam; Nithya Anand; Sajja Chandrasekaran; Yogarajan Kovendhan (Wolters Kluwer Medknow Publications, 2014)
Introduction: Osseointergration defined as the intimate bone-to-implant apposition is the key to implant success and predictability. The primary bone anchorage has long been considered as the gold standard factor and buzzword for successful osseointergration. Bone augmentation and simultaneous implant surgery procedure allow clinicians to reconstruct alveolar bone deficiencies, preserve alveolar dimensions, and replace missing teeth with dental implants in a prosthetically driven position with natural appearance and function. Case Report: This paper reports a case where primary stability although compromised during initial placement, the use of bone graft with platelet-rich fibrin (PRF) combined with stringent maintenance and elimination of micromovements leads to a successful outcome. Six months postoperative findings showed a stable implant with good soft and hard tissue augmentation. Discussion: Primary stability though considered to be a gold standard factor in implant success is not a sole requisite. Achieving secondary stability is the long-term goal, and a combination of stringent maintenance and minimal micromovements will make it achievable.